An Epidemiologic Study of Childhood Atopic Dermatitis in Sleman District, Indonesia: Prevalence and Determinants in the Urban and Rural Areas - Niken Trisnowati; Agnes Tasia Valentine; Adissa Tiara Yulinvia (Faculty of Medicine, Universitas Airlangga, 2026)
Background: The incidence of atopic dermatitis (AD) has increased worldwide; however, it displays differing patterns according to age group and geographic location. This study aimed to assess the prevalence of AD among children in the Sleman area, as well as the correlation between urban and rural environments and the incidence of AD. Methods: This study was conducted in the Sleman district with the Sleman Health and Demographic Surveillance System. The participants were children aged 2 months to 12 years. The collected data comprised family income, parental education, household size, air pollution, and pet ownership. The diagnosis of AD was determined using the ISAAC study criteria for older children and the CEQ for younger children. The prevalence of AD across all participants, as well as within urban and rural categories, was calculated. The disparities in AD determinants between urban and rural settings were examined utilizing the Chi-square test. Result: A total of 1,178 out of 1,191 children were polled in this study. The incidence of AD was 1.36%. The prevalence of AD was 1.3% in urban regions and 1.7% in rural areas (p>0.05). The determinants of AD in urban and rural regions were not significantly different (p>0.05). The prevalence of AD was consistent throughout urban and rural locations, indicating that these environments did not influence AD prevalence in the Sleman district. No substantial difference existed between AD determinants in urban and rural locations. Conclusion: There was no association between urban-rural areas and the prevalence of AD in the Sleman district.